TINGKAT KEPUASAN PASIEN MASKIN RAWAT INAP KELAS III TERHADAP PELAYANAN UNIT PROGRAM ASKESKIN DI RSUD TANGERANG - , Madsubli Kusmana, drs ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : A study on satisfaction of patients from poor communities is an indicator of Askeskin Program at Tangerang Hospital to measure quality for the sustainability of the program. The study can identify patient dissatisfaction so that Tangerang District Government and Hospital have the capacity to make correction. Objective :To identify association between characteristics and patientsâ satisfaction,evaluate satisfaction of patients from poor communities with services provided by the hospital, Identify factors affecting satisfaction of patients from poor communities with the service provided. In other words the study aimed to identify satisfaction of patients from poor communities and find our association between patientsâ characteristics and satisfaction of patients from poor communities at Tangerang Hospital. Method: The study was descriptive using cross sectional survey design. Subject of the study were patients from poor communities hospitalized at Class III ward of Tangerang Hospital. The independent variable was characteristics of respondents comprising age, gender, education, occupation, and types of disease. The dependent variable was satisfaction with the service as described from the dimension of tangibles, reliability, responsiveness, assurance and emphaty. Analysis used Cartesius diagram to evaluate quality of service. Result : Average score of patientsâ satisfaction overall was still below 3.5. This meant that patientsâ satisfaction belonged to medium category. Cartesius diagram showed that the dimension of tangibles and reliability gave satisfaction to patients, but other dimensions of quality, i.e. Responsiveness assurance and emphaty had not given satisfaction. There was significant association (p<0.06) in satisfaction and the service based on education and age group. Meanwhile other characteristic such as gender, occupation and types of disease had no significant association with satisfaction of patients from poor communities at Tangerang Hospital. Conclusion : Satisfaction of patients from poor communities belonged to quite satisfied. Dimension of tangibles, and reliability gave satisfaction but responsiveness, assurance and emphaty had not given satisfaction to patients. There was significant association between education and age group and satisfaction of patients from poor communities at Tangerang Hospital. Suggestion : Tangerang Hospital should increase quality of service. A further experiment was needed with intervention on quality of service and hospital staff.